Recovered memories in context Thoughts and elaborations on Bowers and Farvolden (1996). [article]. - Pennebaker, James W.
The recovered memory debate exposes several traditional and recent contradictions within psychology. Building on K. Bowers and P. Farvolden ( see record 83:27619), the nature of recovered memories has profoundly different meanings for therapeutic versus legal settings. Whereas memory can be distorted during the process of retrieval, certain techniques?such as nondirective writing?may be helpful in reducing suggestive influences in recall. Ironically, methods that have been found to produce the most accurate recollections of the past appear only subtly different from those that yield the greatest distortions. The recovered memory debate must ultimately be viewed within a cultural context, both in terms of the phenomenon and its treatment. The authors discuss parallels to other explanatory and therapeutic fads related to states of nonspecific distress. -- (from the author)